A Systematic Review of the Outcome Evaluation Tools for the Foot and Ankle. Issue 5 (October 2019) - Shazadeh Safavi, Pejma; Janney, Cory; Jupiter, Daniel; Kunzler, Daniel; Bui, Roger; Panchbhavi, Vinod K.
Background . The goal of this systematic review is to determine the most commonly used outcome measurement tools used by foot and ankle specialists and determine their limitations, such as whether they are validated, have floor/ceiling effects, and so on. Methods . A literature search was conducted to identify primary publications between January 1, 2012 and July 1, 2017 that concern care of the foot and ankle and use any established grading criteria to evaluate patients. Results . In 669 publications, 76 scoring systems were used. The 10 most common were American Orthopaedic Foot and Ankle Score (AOFAS), visual analog scale (VAS), Short Form–36 (SF-36), Foot Function Index (FFI), Foot and Ankle Outcome Score (FAOS), Foot and Ankle Ability Measure (FAAM), SF-12, Short Musculoskeletal Function Assessment (SMFA), Ankle Osteoarthritis Scale (AOS), and Foot and Ankle Disability Index (FADI). AOFAS was used in 393 articles, VAS in 308, and SF-36 in 133 publications. AOFAS, VAS, and SF-36 were used to evaluate 23, 352, 20, 759, and 13, 184 patients respectively. AOFAS and VAS were used simultaneously in 172 publications. Conclusion . While there are many different scoring systems available for foot and ankle specialists to use to assess or demonstrate the effectiveness of treatments, the AOFAS, while it is an unvalidated scoring system, is the most commonly used scoring system in this review. Clinical Relevance . This review presents data about commonly used patient reported outcomes systems in foot and ankle surgery. Levels of Evidence: Level III: Systematic review.